Microstructure-property relationships of 420 stainless steel fabricated for by laser-powder bed fusion - GÜLSOY, HAMİT ÖZKAN (ELSEVIER, 2019)
In this study, we report the mechanical properties, microstructure and corrosion behavior 99+ % dense 420 stainless steel parts fabricated by laser-powder bed fusion (L-PBF). As-printed L-PBF parts exhibited an ultimate tensile strength of 1050 +/- 25 MPa, yield strength of 700 +/- 15 MPa, an elongation of 2.5 +/- 02% and a hardness of HRC 55 +/- 1. After the heat treatment operation at 315 degrees C, the ultimate tensile strength improved significantly to 1520 +/- 30 MPa, yield strength increased to 950 +/- 20 MPa, and elongation increased to 63 +/- 0.2% respectively whereas hardness remained at HRC 53 +/- 1. These properties are higher than previously reported literature values for 420 stainless steel fabricated by L-PBF, metal injection molding and powder metallurgy routes. The microstructure indicated a mixture of martensite and retained austenite phases in the as-printed parts. After heat treatment, the microstructure was richer in tempered martensitic laths that is consistent with the enhancement of ultimate tensile strength, yield strength, and elongation without appreciable change in hardness. The corrosion behavior of the as-printed L-PBF parts exhibited a corrosion current of 2.85 +/- 0.4 mA.cm(-2), a polarization resistance of 17,100 +/- 520 Omega.cm(-2) and a corrosion rate of 28 +/- 2 mu m/year which were comparable to the corrosion properties of wrought 420 stainless steel. A significant increase in pitting potential (170 mV) was obtained after the heat treatment. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Laser- powder bed fusion; 420 Stainless Steel; Tensile Strength; Microstructure; Corrosion Properties; MECHANICAL-PROPERTIES; HEAT-TREATMENT; BEHAVIOR; RESISTANCE; MODEL